SNH Arylamination of 3-Nitropyridine: A Competitive Formation of 2-Arylamino-5-nitropyridines and 2-Arylamino-5-nitrosopyridines - Borovlev, Ivan V.; Demidov, Oleg P.; Amangasieva, Gulminat A.; Avakyan, Elena K.; Borovleva, Anastasia A.; Pobedinskaya, Diana Yu. (Synthesis, 2018)
Arylamination of 3-nitropyridine via the nucleophilic substitution of hydrogen leads to a mixture of 2-arylamino-5-nitropyridines and novel 2-arylamino-5-nitrosopyridines, with the latter as the major product. The proposed mechanism includes the formation of σH-adducts and their further aromatization proceeding either through an oxidative pathway or intramolecular Red/Ox pathway of the SNH reaction. Moreover, we have shown that nitroso compounds can be selectively oxidized with m-chloroperbenzoic acid to give the corresponding nitro derivatives or their N-oxides, depending on the reaction temperature and the amount of oxidant.
Keywords: C–H functionalization; SNH arylamination; 3-nitropyridine; metal-free synthesis